2017
DOI: 10.1590/1806-9282.63.06.521
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic performances of serum procalcitonin in patients with bloodstream infections: A parallel, case-control study comprising adults and elderly

Abstract: Diagnostic anD prognostic performances of serum procalcitonin in patients with blooDstream infections: a parallel, case-control stuDy comprising aDults anD elDerly rev assoc Med Bras 2017; 63 (6) Objective: To examine the diagnostic and prognostic performances of serum procalcitonin (PCT) in adult and elderly patients with bloodstream infections (BSIs). Method: A total of 176 patients with culture-proven BSIs and 200 healthy counterparts were studied prospectively. Participants were studied in two adult (age≤6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In numerous studies, levels of PCT, C-reactive protein (CRP), neutrophil-lymphocyte ratio (NLR), and total leukocyte count (TLC) were significantly elevated in patients with positive bacterial growth cultures compared to negative cultures [4,8,11]. Escherichia coli and Staphylococcus aureus were prominently isolated organisms within cultures reported by various studies [4,8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In numerous studies, levels of PCT, C-reactive protein (CRP), neutrophil-lymphocyte ratio (NLR), and total leukocyte count (TLC) were significantly elevated in patients with positive bacterial growth cultures compared to negative cultures [4,8,11]. Escherichia coli and Staphylococcus aureus were prominently isolated organisms within cultures reported by various studies [4,8].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple studies have been regulated in detecting the role of inflammatory mediators in diagnosing sepsis in severely ill trauma patients. In miscellaneous studies, the mean age of significantly ill traumatic patients suffering from sepsis ranged from 40 to 71 years, making it prevalent in the middle-aged and elderly population [4,8,10,11]. Sepsis in sufferers of trauma displayed genetic affinity towards males compared to females [8,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four papers focused on patients with speci c sepsis, such as patients with acute abdominal sepsis [37] , ventilator-associated pneumonia [47] , and postoperative sepsis [45,62] . Two articles addressed elderly patients with sepsis (aged > 65 [55] and > 85 years [60] ), whereas another study [52] included patients aged ≤ 65 and > 65 years. Two studies [18,33] reported separately cases of positive and negative blood cultures.…”
Section: Study Characteristicsmentioning
confidence: 99%